Acute Dengue Myositis in a 6 Years Old Boy: An Uncommon Complication of a Common Disease - Sanchayan Sinha; Anannya Ghosh (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
Introduction: Dengue fever is an arboviral disease caused by the dengue virus transmitted by the bite of female Aedes aegypti mosquitoes, affecting people worldwide and often causing pandemics in Southeast Asian countries. The global health disease burden of dengue has been found to be the highest among all arboviral diseases. Dengue viral infection symptoms range from flu-like illness to complications like pneumonia, hepatitis, neurologic symptoms like encephalitis, myopathy, Guillain–Barre syndrome, phrenic neuropathy, subdural hematoma, and cerebral vasculitis. The possibility of skeletal muscle invasion causing myositis is another rare entity. Case Description: A case of dengue, with myositis presenting as muscle weakness, decreased power, and raised Creatinine Phosphokinase (CPK) level in a 6-year-old boy has been reported. The boy suffered from Dengue viral fever diagnosed by positive NS1 antigen. Initially, the symptoms were like uncomplicated dengue fever but later he developed leg muscle pain and, a decreased range of movements. The Serum CPK level was increased and then the baby was diagnosed with myositis. Later with supportive treatment, he improved, the pain subsided, the power and tone of leg muscles increased and the serum CPK level came to normal. The child’s condition was self-limiting and hence he was treated as per standard dengue national management guidelines with antipyretics and regular monitoring of blood pressure, hematocrit, platelet count, and level of consciousness. Conclusion: Myositis in the pediatric population is a rare entity and hence often neglected and undertreated. It can turn into permanent damage and deformity if not treated in time in long-term sequelae.